Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Ribeiro, Márcio Garcia [UNESP]; Pereira, Thiago Tourinho [UNESP]; de Lima Paz, Patrik Júnior [UNESP]; de Almeida, Beatriz Oliveira [UNESP]; Cerviño, Carmen S. Araújo [UNESP]; Rodrigues, Carolina Aparecida [UNESP]; Santos, Gabrielly Terra Sartori [UNESP]; de Souza Freire, Larissa Maria [UNESP]; Portilho, Fábio Vinicius Ramos [UNESP]; Filho, Marcelo Fagali Árabe [UNESP]; Paschoal, Natália Rodrigues [UNESP]; Bello, Thaís Spessotto [UNESP]; et al. (Springer Nature, 2023)
Central nervous system (CNS) infections comprise life-threatening clinical conditions in domestic species, and are commonly related to severe sequelae, disability, or high fatality rates. A set of bacterial pathogens have been identified in central nervous infections in livestock and companion animals, although the most of descriptions are restricted to case reports and a lack of comprehensive studies involving CNS-related bacterial infections have been focused on a great number of domestic species. In this scenario, we retrospectively investigated selected epidemiological data, clinical findings, bacteriological culture, and in vitro susceptibility patterns of 136 nonrepetitive neurologic cases in domestic species (2005–2021). Bacterial isolates were recovered from 25% (34/136) of the cerebrospinal fluid (CSF) sampled. The isolates were obtained from cattle (9/136 = 6.6%), dogs (7/136 = 5.1%), horses (6/136 = 4.4%), goats (3/136 = 2.2%), pigs (3/136 = 2.2%), sheep (3/136 = 2.2%), cats (2/136 = 1.5%), and asinine (1/136 = 0.7%). Among animals with bacterial isolation, Staphylococcus aureus (6/34 = 17.6%), Escherichia coli (5/34 = 14.7%), Staphylococcus beta-hemolytic (5/34 = 14.7%), and Trueperella pyogenes (3/34 = 8.8%) were predominant, in addition to a miscellaneous of other bacteria isolated in minor frequency, e.g., Corynebacterium pseudotuberculosis, Enterobacter cloacae, Mannheimia haemolytica, Pseudomonas aeruginosa, and Streptococcus equi subsp. equi. In vitro susceptibility tests of isolates revealed that amoxicillin/clavulanic acid (11/13 = 84.6%), cephalexin (9/11 = 81.8%), and florfenicol (9/12 = 75%) were the most effective antimicrobials. Conversely, isolates exhibited resistance mainly to tetracycline (6/10 = 60%), penicillin (6/11 = 54.5%), and trimethoprim/sulfamethoxazole (5/11 = 45.5%). Also, multidrug resistance to ≥ 3 classes of antimicrobials was found in 23.5% (8/34) strains. Data relative to the outcome was available in 79.4% (27/34) of animals that had bacterial isolation, and from these, the lethality rate was 92.6% (25/27). Incoordination (14/34 = 41.2%), recumbency (11/34 = 32.4%), apathy (10/34 = 29.4%), anorexia (9/34 = 26.5%), blindness (7/34 = 20.6%), seizure (6/34 = 17.6%), limb paresis (5/34 = 14.7%), head-pressing (4/34 = 11.8%), and nystagmus (3/34 = 8.8%) were the most frequent clinical signs. A variety of bacterial pathogens were identified in the CSF of domestic species showing neurologic signs, with a predominance of staphylococci, streptococci, and enterobacteria. High lethality of cases, poor in vitro efficacy of conventional antimicrobials, and a high in vitro multidrug resistance pattern of isolates were seen. Our results contribute to etiological characterization, antimicrobial resistance patterns, and clinical-epidemiological findings of bacterial infections in domestic species with neurological signs.
Keywords: Bacterial etiology; Central nervous infections; Companion animals; Livestock; Multidrug resistance